1988
DOI: 10.1016/s0022-5347(17)42418-9
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of an Inflatable Penile Prosthesis Reservoir into the Bladder, Presenting as Bladder Calculi

Abstract: We report a case of erosion of an inflatable penile prosthesis reservoir int the bladder 4 years after implantation for organic impotence. In contrast to previously reported cases this complication was not associated with incontinence, urinary tract infection or a revision procedure. Microscopic hematuria was present but there was no pyuria. Diagnosis evaded radiographic and cystoscopic confirmation. Bladder erosion of the reservoir was discovered incidentally during treatment of bladder calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In our recent literature review conducted in July of 2013 utilizing PubMed and Medline, we identified 37 cases of nonmechanical reservoir-related complications dating back to 1984. The most common complication was erosion of the reservoir into the bladder; which comprised 15/37 (41%) of the cases [9][10][11][12][13][14][15][16][17][18]. The most common symptom of bladder erosion was hematuria; which was found in 100% of cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent literature review conducted in July of 2013 utilizing PubMed and Medline, we identified 37 cases of nonmechanical reservoir-related complications dating back to 1984. The most common complication was erosion of the reservoir into the bladder; which comprised 15/37 (41%) of the cases [9][10][11][12][13][14][15][16][17][18]. The most common symptom of bladder erosion was hematuria; which was found in 100% of cases.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with prior pelvic surgery, it has been well demonstrated that reservoir placement in the space of Retzius has an increased complication rate. Complications such as bladder erosion, however, exist even in low-risk patients and is the most common of all reservoir complications as demonstrated in Table 1 [9][10][11][12][13][14][15][16][17][18]39,44]. For this reason, ectopic reservoir placement has gained popularity in recent years [25,39].…”
Section: Reservoir Placement Techniquesmentioning
confidence: 99%
“…All experienced implanters have performed cystoscopy on IPP patients and seen the imprint of the reservoir of the superior bladder wall as the bladder fills with irrigation fluid. The literature is replete with case reports of bladder laceration or erosion related to reservoir placement [13–18]. Erosion seems more likely in men with a history of RRP [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Erosion seems more likely in men with a history of RRP [13,14]. Delayed erosion of reservoirs into the bladder has occurred as late as 4 years following IPP placement [15]. Inadvertent placement of reservoir into the bladder at the time of surgery is another complication that has been reported with retropubic placement [19].…”
Section: Discussionmentioning
confidence: 99%
“…Certain predisposing conditions are believed to increase the risk of reservoir erosion, including prior pelvic surgery or radiation. In addition to our case I, there are 17 other cases of reservoir erosion into the bladder that have been published over the past 25 years occurring acutely or remotely after implantation [14][15][16][17][18][19][20][21][22][23]. As an example of a recognized acute bladder laceration, Eldefrawy and Kava presented a 67-year-old man status post radical prostatectomy who underwent placement of an IPP via a transscrotal incision.…”
Section: Erosion Into Visceral Structuresmentioning
confidence: 98%